Imaging dose during the radiotherapy process - Baloyi, Tebogo Daniel (My University, 2018)
OBJECTIVES: This study aimed to investigate the total concomitant imaging dose accumulated from different imaging modalities during the radiotherapy process. The radiation dose resulting from imaging modalities is often neglected because it is viewed as too low compared to high levels of radiation dose normally prescribed for treatment. With recent advances in high dose imaging technology integrated into radiotherapy treatment units, there has been a growing concern regarding the imaging dose as a result of their increased use. DESIGN & METHOD: The study was conducted at the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) and Richards Bay Medical Institute (RBMI). Imaging modalities investigated at CMJAH were fluoroscopy simulation, Computed Tomography (CT) scanning and MV planar imaging. Imaging modalities investigated at RBMI were kV Cone Beam CT, CT scanning and kV planar imaging. CT dosimetry was performed using a head and body phantom with a pencil ionisation chamber. A calibrated parallel plate diagnostic ionisation chamber with a 30 × 30 cm2 acrylic phantom was used for the fluoroscopy simulator and kV planar imaging dosimetry. The total imaging dose was estimated as the sum of dose resulting from each modality taking into account the number of times imaging was performed, on 20 patients from each institution. RESULTS: CMJAH: The measured volume Computed Tomography Dose Index (CTDIvol) was 17.98 ± 1.54 mGy and 20.26 ± 1.64 mGy for head and body scanning protocols respectively. The measured simulator Entrance Surface Air Kerma (ESAK) dose from pelvic imaging protocol for 20 patients of different sizes ranged from 0.16 ± 0.01 mGy to 0.32 ± 0.03 mGy for anterior-posterior/posterioranterior (AP/PA) projections and 1.49 ± 0.13 mGy to 3.18 ± 0.27 mGy for lateral projections. The total dose accumulated during the complete course of treatment from MV portal imaging ranged from 5 cGy to 43 cGy for both AP/PA and lateral projections. The average estimated effective doses to patients resulting from a single planning CT procedure, acquisition of one pair of AP/PA and lateral simulation films and one session of 6 MV portal imaging verification were 7.57 ± 0.61 mSv, 0.19 ± 0.02 mSv and 4.80 ± 0.24 mSv respectively. Based on a series of 20 patients, the calculated average effective dose accumulated during a complete course of treatment were 7.53 ± 0.61 mSv, 0.37 ± 0.03 mSv and 15.53 ± 0.78 mSv respectively from each modality respectively. The greatest contribution to the patient’s total effective dose from imaging alone originated from the planning CT scan. However when taking into account the number of imaging procedures typically prescribed for each modality, the 6 MV portal imaging contributed the highest dose. RBMI: The measured CTDIvol was 79.60 ± 6.61 mGy and 33.79 ± 2.80 mGy for the head and body scanning protocols respectively. For kVCBCT, the CTDIvol measured was 5.20 ± 0.43 mGy and 14.40 ± 1.19 mGy for the head and body scanning protocols respectively. The ESAK measured for kV planar imaging of the head was 0.31 ± 0.03 mGy and 0.12 ± 0.01 mGy for the AP/PA and lateral projections respectively. For AP/PA pelvic imaging the ESAK ranged from 0.16 ± 0.01 mGy to 0.33 ± 0.03 mGy for small to extra-large patients. For lateral imaging the range was 1.49 ± 0.13 mGy to 3.18 ± 0.27 mGy from small to extra-large patients respectively. The estimated average effective dose to 20 patients resulting from the planning CT, kVCBCT and kV portal imaging procedures during the complete course of treatment were approximately 19.96 ± 1.66 mSv, 11.82 ± 0.98 mSv and 1.49 ± 0.12 mSv respectively. The greatest contribution to the total effective dose from imaging alone originated from the planning CT scan. CONCLUSION: The results indicate that considerable dose could be delivered to patients during image guided radiotherapy, primarily when imaging procedures are over utilized and not optimized, adding more burden of dose to the already high levels of dose they receive from their treatment. The dose contribution from the planning CT was the highest and is influenced primarily by the scan length and the number of examinations. This can be reduced if scans are not acquired beyond the region of interest (ROI) required for planning purposes or by adjusting protocols to larger slice spacing outside the ROI. Inadequate scanning of patients can also add more dose to patients if the CT examination is repeated to acquire sufficient image information required for radiation therapy planning. Modern imaging techniques such as kVCBCT applied during patient setup verification, can also add a significant dose when prescribed to confirm setup on a daily basis. kV planar imaging dose was significantly lower than all other imaging modalities researched in this study. Compared with MV planar imaging, the average effective dose to the patient during the complete course of treatment from MV portal imaging was 7.95 ± 0.65 mSv whereas it was 1.49 ± 0.13 mSv from kV portal imaging. Therefore, if the soft tissue image information from MV planar imaging is not justified, kV imaging is recommended. On the other hand, single exposure MV imaging of static treatment ports could be subtracted from the prescribed radiotherapy dose.
A research report submitted partial fulfillment of the Degree of Master of Science in Physics in the field of Medical Physics to the Faculty of Science, University of the Witwatersrand, Johannesburg, in Johannesburg, 2018.
Keywords: Radiotherapy; Cancer--Radiotherapy